Itaipu e as relações brasileiro-paraguaias de 1962 a 1979: fronteira, energia e poder - Espósito Neto, Tomaz (2012)
The objective of this study is to examine the relations between Brazil and Paraguay during the political negotiations on the construction of Itaipu, which had their beginning in 1962 with the release of the Octavio Marcondes Ferraz project, and ended in 1979, with the signing of the Tripartite Agreement, which has consolidated a legal framework in the hydroelectric exploitation in the watershed of ―Rio da Prata‖. This analysis is crucial to the understanding of the Brazilian foreign policy performance and of the interstate power relations surrounding the construction of the hydroelectric plant Itaipu Binational